PENGARUH METODE TREFFINGER DALAM PEMBELAJARAN MENULIS TEKS PERUASIF PADA KELAS VIII SMP - Nur Ana Nur Ana Ana (IKIP Siliwangi, 2020)
Learning is one of the processes of activities that occur in the scope of schools carried out by teachers and students. Based on the syllabus contained in the 2016 Permendikbud, one of the subject matter contained in the 2013 revised 2017 curriculum is writing persuasive texts. Writing persuasive text means producing a text that contains persuasion to influence the reader to do something. Because in writing persuasive texts must be able to influence other people, therefore a method is needed during the learning process so that writing persuasive texts can be done by students in accordance with predetermined rules. The purpose of this study is to determine the effect of the treffinger method in learning persuasive text writing skills. Writing is an aspect of the skill used to communicate indirectly. In this study using the one group method with pretest-posttest design. The research stamp was 43 students of class VIII F. Data collection tools used were lesson plans, observation sheets and test questions. Pretest and posttest results showed an increase in persuasive text writing skills using the Treffinger method. The results of this study indicate the effect of increasing persuasive text writing skills using the Treffinger method in accordance with the purpose text of this study.